Facile self-propagated carbonization synthesis of phosphorus-doped carbon-based catalysts for partial oxidation and hydrogenation. Issue 16 (26th July 2022) - Wang, Huan; Wang, Weitao; Jiang, Xulu; He, Zhen-Hong; Wang, Kuan; Yang, Yang; Liu, Zhao-Tie; Han, Buxing
Abstract : A self-propagated carbonization method to prepare phosphorus-doped carbon materials has been developed. Abstract : In this work, a fast and self-propagated carbonization (SPC) method to prepare phosphorus-doped carbon (PDC) and hybrid materials is proposed. PdZr/PDC prepared by the SPC method has good catalytic performance for both partial oxidation of benzyl alcohol to benzaldehyde and partial hydrogenation of phenol to cyclohexanone. The method has some obvious advantages, such as being simple and clean, and can be used easily for the large-scale preparation of the materials.